A Contribution to Knowledge of Craterellus (Hydnaceae, Cantharellales) in China: Three New Taxa and Amended Descriptions of Two Previous Species - Zhang, Yu-Zhuo; Zhang, Ping; Buyck, Bart; Tang, Li-Ping; Liang, Zhi-Qun; Su, Ming-Sheng; Hao, Yan-Jia; Huang, Hong-Yan; Zhang, Wen-Hao; Chen, Zuo-Hong; Zeng, Nian-Kai (Frontiers in Microbiology, 2022)
Species of Craterellus (Hydnaceae, Cantharellales) in China are investigated on the basis of morphological and molecular phylogenetic analyses of DNA sequences from nuc 28S rDNA D1-D2 domains (28S) and nuc rDNA internal transcribed spacer ITS1-5.8S-ITS2 region. Five species are recognized in China, three of them are described as new: C. fulviceps, C. minor, and C. parvopullus, and two of them are previously described taxa: Cr. aureus, and C. lutescens. A key to the known Chinese taxa of the genus is provided.